2001
DOI: 10.1139/v01-047
|View full text |Cite
|
Sign up to set email alerts
|

New pathways of site selective aromatic alkylation of palladium complexes: fragmentation to arenes vs. ring closure to hexahydromethano-fluorenes or -phenanthrenes

Abstract: Dimeric arylbicycloheptylpalladium halide complexes of type 1 undergo selective alkylation at the aromatic site by reaction with allyl, styryl, and benzyl bromides (RBr) via hexahydromethanopalladafluorenes (2). Ring closure of the resulting palladium complex (7) on sp2 and sp3 C-H bonds of a suitable R group then occurs with formation of hexahydromethanophenanthrene or hexahydromethanofluorene derivatives. Alternatively, substituted arenes derived from bicycloheptene deinsertion are formed. In some cases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…To our delight, the replacement of methyl isonicotine with triphenylphosphine successfully afforded the coupling product trisubstituted olefin Z - 4a in 25% yield along with 5.6% of E isomer 4aa (Table , entry 2). The configurations of Z - 4a and E - 4aa were confirmed by 1 H NMR analysis (see Supporting Information (SI)) . By carefully screening the conditions (see SI, Tables S1 and S2), we found that the phosphine ligand was crucial for the reaction, and no desired product was obtained in the absence of phosphine ligand (Table , entry 4).…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…To our delight, the replacement of methyl isonicotine with triphenylphosphine successfully afforded the coupling product trisubstituted olefin Z - 4a in 25% yield along with 5.6% of E isomer 4aa (Table , entry 2). The configurations of Z - 4a and E - 4aa were confirmed by 1 H NMR analysis (see Supporting Information (SI)) . By carefully screening the conditions (see SI, Tables S1 and S2), we found that the phosphine ligand was crucial for the reaction, and no desired product was obtained in the absence of phosphine ligand (Table , entry 4).…”
Section: Resultsmentioning
confidence: 80%
“…According to the literature , and the above observed results, a plausible mechanism is proposed in Scheme . First, the reaction of aryl iodide with norbornene in the presence of Pd(0) and base produces a five-membered palladacycle A , which coordinates with ( E )-vinyl bromide followed by oxidative addition to generate an arylpalladium species B .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations